Educational Challenges in Pakistan: Facts or Falsity (Journal of Social Sciences Review, 2021)
Education lays the basis for every country's political, social, and economic growth. A sustainable school framework allows the country to accomplish national targets. As a developing world, Pakistan has faced crucial educational problems since its birth, so the education system has struggled to perform on the nation's expectations. Different variables are responsible for this situation. This study unfolds problems confronting Pakistan's education sector. Education is the primary driver when we speak about leadership and growth that improves the individual and pushes the country towards political, social, and economic living standards. Until now, schooling at any stage trains the individual for the next level until he brings the person to tertiary industry; therefore, there is a strong link with Pakistan's education and growth; obviously, the indicator doesn't reflect positive outcomes. There is an untrained teaching workforce with fluctuating enrollments and limited-resource facilitation, a dual educational medium, inadequate assessment mechanism, and government allocating low budgets to the education system. Moreover, there is a shortage of study that encourages innovative methods of handling decision-making, and gender inequality is often seen as an issue that cannot be ignored, so this subject is chosen as a domain to focus on and advice to address.
Keywords: development, education, educational budget, educational problems, Pakistan